2016
DOI: 10.1007/s11130-016-0554-5
|View full text |Cite
|
Sign up to set email alerts
|

Common Bean Leaves as a Source of Dietary Iron: Functional Test in an Iron-Deficient Rat Model

Abstract: Recent findings made by our group indicate that the iron content in Phaseolus vulgaris leaves is at least four times greater than in grains therefore, we evaluated the effect of supplementation with bean leaf (iron content of 275 mg/kg on a dry basis) in iron-deficient rats. Anemia was induced by feeding rats with an iron-deficient diet (IDD) for 11 days and iron-recovery diets were subsequently tested for 14 days using a normal diet, a 10 % bean leaf-supplemented IDD (BLSD) or a ferrous sulfate-supplemented I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Amylase inhibitor from WKB reduced hyperglycemia in diabetic rats [10]. Comparative evaluation between meals prepared from lentils or WKB in anemic rats showed that WKB extremely enhanced iron bioavailability and liver store than lentils [11]. WKB non-digestible fibers have been shown to improve an early stage of colorectal cancer by modulating signaling pathway genes in rats [12].…”
Section: Introductionmentioning
confidence: 99%
“…Amylase inhibitor from WKB reduced hyperglycemia in diabetic rats [10]. Comparative evaluation between meals prepared from lentils or WKB in anemic rats showed that WKB extremely enhanced iron bioavailability and liver store than lentils [11]. WKB non-digestible fibers have been shown to improve an early stage of colorectal cancer by modulating signaling pathway genes in rats [12].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Martínez-Zavala et al [25] about the iron content in the bean plant leaves (Phaseolus vulgaris), a recovery of hematic biomarkers was observed, such as hemoglobin, erythrocyte count, and hematocrit in rats with induced anemia, when diets with iron source from this legume were administered.…”
Section: Vegetable Sources Of Iron and Its Bioavailabilitymentioning
confidence: 97%
“…Bean leaves are rich in iron and can be used as a treatment for iron deficiency. Using a rat model of induced anemia, Martínez-Zavala et al used a diet enriched in bean leaves to recover the correct blood cell population percentage [73].…”
Section: Nutritional Sources Of Ironmentioning
confidence: 99%
“…Nowadays, foods that possess high concentrations of nutrients, limited caloric content and show antioxidant and anti-inflammatory properties are often called superfoods by nutritionists and media [145,146]; nevertheless, they are often overlooked on food stores shelves. Some examples include foods like milk rich in calcium and minerals derived from unconventional animals like camel [147] and donkey [148,149], berries [150] and scarcely cultivated vegetables or vegetable parts that are discarded during food processing [73], indigenous vegetables [151] sustainable, and nutritious diets, as well as omega-3 fatty acids from fish or nuts. The potential benefits of superfoods have great margins of employment in the treatment of chronic inflammation [48,152] or as supplements in healthy dietary patterns [153].…”
Section: Superfoods As Nutritional Strategies For Iron Level Replenismentioning
confidence: 99%